Revision of PV2 criteria based pedestrian crossing warrants - Jain, Udit; Rastogi, Rajat (Transport, 2020)
Several guideline documents on pedestrian crossing warrants are followed around the world. Peak hour pedestrian volume “P” and vehicular volume “V” are two most commonly used factors in these guidelines. PV2 is a criteria, which is used in guideline documents of India, Iran and UK to identify the need of warranting a particular mid-block location. In India, these guidelines were adapted from UK in 1988 and have not been revised in the last three decades. These guidelines report a benchmark value, in the excess of which a location should be warranted. The benchmark values are based on peak flows of 1980s, which have increased drastically over the years. In addition, the guidelines do not identify the type of crossing facility, which should be provided at a particular location. Therefore, these guidelines need to be revised. In this paper, PV2 matrices have been developed for a variety of road configurations using the maximum field hourly flows as the upper bounds. Further, probability distributions have been fitted to the PV2 values. Threshold values have been proposed based on the curvilinear characteristics of the probability distributions. The revised PV2 values vary from 0.6×108 to 2.1×1011 for different roadway configurations. The ranges formed using these values have been used to classify the type of crossing facility to be installed using a systematic hierarchical approach. The warrant charts and PV2 value ranges can be used to identify the need, as well as the most appropriate crossing facility for the site based on the peak hour pedestrian volume and vehicular volume. The proposed PV2 values and warrants are based on Indian traffic flow conditions. These threshold values may require modifications for application in any other country.